Cartografías cosmopolitas León de Greiff y la tradición literaria - Ramírez Rojas, Marco (Purdue Studies in Romance Literatures, 2023)
Tradición literaria y cartografías cosmopolitas: la poesía de León de Greiff is an in-depth study of the literary production of the mid-20th century Colombian writer León de Greiff. This book analyses his poetic works as a complex manifestation of literary cosmopolitanism and a challenging elaboration of cultural cartographies. The study of these elements offers a novel approach to an unexplored aspect of De Greiff's poetry. Through a careful reading of De Greiff's seemingly disorganized assimilation of French, Spanish, English, Middle Eastern, East Asian, and Northern European literary traditions, Ramírez Rojas understands his literature as a capricious self-fashioning of a poetic genealogy. This practice challenges the classical notion of tradition and displays an alternative practice of self-creation of a literary lineage that goes beyond the borders of national affiliation, linguistic proximity, and historical continuity. This book proposes to read León de Greiff's poems as cultural maps that reveal both a desire of connectivity with the world and a need for reorganizing the imaginary library of world literature. Ramírez Rojas contends that the haphazard collection, accumulation, and rearrangement of elements derived from various cultural sources challenges the logics of local versus global affiliations. Similarly, as León de Greiff builds a worldwide network of connections from a self-assumed position of eccentricity, his works dispute the binary division of cultural centers and peripheries, revendicating marginality as a productive condition. The study of this alternative cosmopolitanism brings de Greiff's writings into current debates about Latin American's cultural positionality within the frame of cosmopolitanism and world literature.Tradición literaria y cartografías cosmopolitas: la poesía de León de Greiff es un estudio de la producción poética de este escritor colombiano de mediados del siglo XX. En este libro se estudian sus textos como complejas manifestaciones de un cosmopolitismo literario y como arriesgadaa elaboraciones de cartografías poéticas. El análisis de estos elementos ofrece una nueva perspectiva de acercamiento a una temática todavía inexplorada en la obra de León de Greiff. Por medio de una cuidadosa lectura de su aparentemente caprichosa asimilación de fuentes francesas, españolas, inglesas, de medio y lejano oriente, así como también de sus fuentes escandinavas, Ramírez Rojas propone comprender la literatura greiffiana como una tarea de elaboración de una genealogía poética propia. Esta práctica cuestiona las nociones clásicas de tradición y pone en marcha un ejercicio alternativo de autoconstrucción de un linaje literario que no está limitado por fronteras nacionales, proximidad lingüística ni continuidad histórica. Este estudio plantea la posibilidad de leer los poemas de León de Greiff como mapas culturales que revelan tanto un deseo de conectividad con el mundo como una necesidad de reorganizar la biblioteca imaginaria de la literatura mundial. Ramírez Rojas propone que la azarosa acumulación y reestructuración de elementos derivados de distintas cuentes culturales pone en cuestión las lógicas de afiliación global vs. afiliación local. De igual forma, dado que de Greiff construye una red de conexiones a partir una posición de auto-asumida excentricidad, sus trabajos poéticos disputan las divisiones binarias entre centros y periferias culturales, reivindicando la marginalidad como una condición productiva. El estudio de esta manifestación de cosmopolitismo alternativo inscribe su poesía en los debates actuales sobre el posicionamiento cultural de Latinoamérica dentro del espacio cosmopolita y los círculos de la literatura mundial.